1 IL-18: a serological biomarker to discriminate AOSD from sepsis. (23rd January 2014) - Priori, R.; Colafrancesco, S.; Minniti, A.; Alessandri, C.; Perricone, C.; Iaiani, G.; Valesini, G.
Abstract : Background: A great challenge in clinical practice is the differential diagnosis between rheumatic inflammatory diseases, such as Adult Onset Still's disease (AOSD), and sepsis. Indeed, these conditions share several clinical and laboratory findings. Recent studies have investigated the cytokine profile in patients with AOSD and sepsis detecting elevated serum levels of different cytokines, including interleukin (IL)-18. This cytokine plays a pivotal role in AOSD, by driving the inflammatory process. Objectives: To investigate IL-18 serum levels in AOSD and to assess whether IL-18 could be used as a biomarker to discriminate between patients with AOSD and sepsis. Methods: We measured IL-18 serum levels by a commercial ELISA kit (Immuno Pharmacology Research, Italy), in a cohort of patients with AOSD (diagnosed according to Yamaguchy criteria) and in patients sepsis (diagnosed according to American College of Chest Physicians/Society of Critical Care Medicine Consensus Conference). In AOSD, disease activity was evaluated with Rau's criteria, and patients were defined "active" if they scored ≥4. Area under the receiver operating characteristic curve (ROC-AUC) analysis was used to evaluate the diagnostic utility of the IL-18. Results: Thirty patients with AOSD (F 18, M 12, mean age 39.6 years, range 18-69) and 7 patients with sepsis (F 4 M 3, mean age 35.1 years, range 30-55) were enrolled. Mean IL-18 serum level in AOSD patients [1298.7 pg/ml (range 0–6015)] was significantly higher from mean IL-18 serum level in sepsis [113.5 pg/ml (range 52–328), P=0.008]. ROC-AUC analysis of the serum concentration of IL-18 indicated that it was significantly diagnostic of AOSD, especially when active. The ROC-AUC analysis for the serum level of the IL-18 between patients with AOSD and sepsis was 0.712. At a cutoff point of 179 pg/ml, corresponding to the greatest sum of specificity and sensitivity, the specificity was 69.7% and the sensitivity was 87.5% for detection of AOSD (likelihood 2.89). When disease activity was scored according to Rau's criteria, 21/30 (70%) patients were identified as active. These patients showed mean IL-18 serum levels (1793 pg/ml, range 0-6015) significantly higher than patient with "non active" disease (145.5 pg/ml, range 0-685, P=0.0039), as well as higher than sepsis (P=0.007). The ROC-AUC analysis for the serum level of the IL-18 between active patients with AOSD and sepsis was 0.845. At a cutoff point of 223 pg/ml, the specificity was 87.5% and the sensitivity was 80.9% for detection of AOSD (likelihood 6.48). Conclusions: A significant difference in IL-18 serum levels between patients with AOSD and sepsis was found, especially in those patients with active disease. This evidence may confirm the potential utility of IL-18 in the differential diagnosis between AOSD and sepsis. Disclosure of Interest: None Declared